Pengembangan Trainer Sensor dan Transduser di Program Studi Pendidikan Vokasional Mekatronika Fakultas Teknik Universitas Negeri Makassar - Putri Putri; Syahrul Syahrul; Hendra Jaya (JURNAL NALAR PENDIDIKAN, 2022)
This study aims to determine the stages of developing sensor and transducer trainers and aims to produce practical, valid and effective trainers in the Mechatronics Vocational Education Study Program.  The type of research used in this research is Research and Development (R&D) with the development model of Computer Assisted Instruction (CAI): (1) Needs Assessment, (2) Design, (3) Development and Implementation  (development and implementation), (4) Evaluation and revision (evaluation and revision).  The results of this study obtained that trainer sensors and transducers developed in the media aspect obtained a total rating of 93.28% for the first category (very valid) to be used then the material (module) 87.63% for the second category (valid).  At the trainer implementation stage, the average overall student response was 82.88%, which was in the second category (practical) to use.  While the results of student test scores before the use of trainer sensors and transducers the percentage obtained was 54.97% and after the use of trainer sensors and transducers 78.62% experienced an increase in understanding, with an N-Gain of 0.52 in the second category (medium).  This study concludes that the sensor and transducer trainers developed are valid, practical and effective for use in the Mechatronics Vocational Education Study Program.